Kurangnya Minat Belajar Siswa Pada Masa Pandemi Covid-19 Di SMP Negeri 2 Kampung Rakyat - Adinda Kartika Sari (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
This research uses qualitative research. This qualitative research is descriptive in nature using observational analysis and interviews so that it becomes an easy-to-understand research. The learning process at SMP Negeri 2 Kampung Rakyat in this study uses an online learning process or referred to as distance learning (from home) which is guided by parents and teachers at school. Students do online learning and interact with teachers using several applications such as Zoom, Google Meet, Google Classroom, Whatsapp Group, and Google Form. This study aims to determine the lack of interest in student learning during the COVID-19 pandemic at SMP Negeri 2 Kampung Rakyat. The object of this research is two students from the school. The results of this study indicate that the online learning process during the COVID-19 pandemic at the SMP Negeri 2 Kampung Rakyat school greatly affected students' interest in learning, so that students felt bored and unmotivated because they did not meet their friends and teachers directly.